2008
DOI: 10.1074/jbc.m802973200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant Human Prolyl 3-Hydroxylase Isoenzyme 2, an Enzyme Modifying the Basement Membrane Collagen IV

Abstract: The single 3-hydroxyproline residue in the collagen I polypeptides is essential for proper fibril formation and bone development as its deficiency leads to recessive osteogenesis imperfecta. The vertebrate prolyl 3-hydroxylase (P3H) family consists of three members, P3H1 being responsible for the hydroxylation of collagen I. We expressed human P3H2 as an active recombinant protein in insect cells. Most of the recombinant polypeptide was insoluble, but small amounts were also present in the soluble fraction. P3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 30 publications
2
78
0
Order By: Relevance
“…It is possible therefore that the non-A1 sites in A-clade and B-clade collagen chains are not hydroxylated by P3H1. However, P3H1 does seem to be the main isoform expressed by cells that make fibrillar collagens, whereas P3H2 is most prominently expressed in basement membrane-rich tissues (5). Alternatively the non-A1 3Hyp sites may not require the same enzyme complex as site A1.…”
Section: Comparison Of A-clade and B-clade 3hypmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible therefore that the non-A1 sites in A-clade and B-clade collagen chains are not hydroxylated by P3H1. However, P3H1 does seem to be the main isoform expressed by cells that make fibrillar collagens, whereas P3H2 is most prominently expressed in basement membrane-rich tissues (5). Alternatively the non-A1 3Hyp sites may not require the same enzyme complex as site A1.…”
Section: Comparison Of A-clade and B-clade 3hypmentioning
confidence: 99%
“…Three different genes encoding P3H1, P3H2, and P3H3 are present in the human genome, which show tissue specificity in their expression (4,5). Substrate proline residues occur in a prerequisite sequence -Pro-4Hyp-Gly.…”
mentioning
confidence: 99%
“…Thus, the 106 Y-position Hyp residues reported here are likely 4-Hyp. Gly-Pro-Hyp triplets are thought to constitute the substrate sequence for P3Hs, of which there are three (55,56). We conclude the 22 Hyp residues in the X-position of Gly-Hyp-Hyp triplet repeats in the COL1 domain of bovine placental ␣1(V) chain are likely to be 3-Hyp residues.…”
Section: Ptms Of Bovine Placental ␣1(v)mentioning
confidence: 99%
“…Limited information is available about the substrate specificity of the P3H2 and P3H3 members of the family. Although cell culture studies have indicated that P3H2 exhibits some activity toward fibril-forming collagens (7), type IV collagen was suggested as the main substrate of this enzyme (8).…”
mentioning
confidence: 99%